2017
DOI: 10.1002/eji.201646885
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory 2B4 contributes to NK cell education and immunological derangements in XLP1 patients

Abstract: X-linked lymphoproliferative disease 1 (XLP1) is an inherited immunodeficiency, caused by mutations in SH2D1A encoding Signaling Lymphocyte Activation Molecule (SLAM)-associated protein (SAP). In XLP1, 2B4, upon engagement with CD48, has inhibitory instead of activating function. This causes a selective inability of cytotoxic effectors to kill EBV-infected cells, with dramatic clinical sequelae. Here, we investigated the NK cell education in XLP1, upon characterization of killer Ig-like receptor (KIR)/KIR-L ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…In this session chaired by Jens Kieckbusch, Daniela Pende showed that NK cells from patients with X‐linked lymphoproliferative disease have a defective phenotypic repertoire with a substantial proportion of the cells lacking self HLA class I specific inhibitory receptors compared with healthy controls . Their results showed that, in patients with X‐linked lymphoproliferative disease, the inhibitory 2B4/CD48 pathway contributes to NK cell education and could play a role in preventing killing of CD48 + Epstein–Barr virus‐infected cells.…”
Section: Nk Cell Educationmentioning
confidence: 99%
“…In this session chaired by Jens Kieckbusch, Daniela Pende showed that NK cells from patients with X‐linked lymphoproliferative disease have a defective phenotypic repertoire with a substantial proportion of the cells lacking self HLA class I specific inhibitory receptors compared with healthy controls . Their results showed that, in patients with X‐linked lymphoproliferative disease, the inhibitory 2B4/CD48 pathway contributes to NK cell education and could play a role in preventing killing of CD48 + Epstein–Barr virus‐infected cells.…”
Section: Nk Cell Educationmentioning
confidence: 99%
“…This represents an unexpectedly large number of theoretically uneducated NK cells and would at first glance seem like a high amount of inefficiency in how the body produces effector NK cells. However, recent studies in both mice and humans indicate that other receptors, such as the SLAM family receptors 2B4 and SLAMF6, can also mediate NK cell education in addition to KIRs and CD94/NKG2A (Chen et al, 2016a; He and Tian, 2017; Meazza et al, 2017; Wu et al, 2016). Furthermore, there is also recent evidence that educated and uneducated NK cells can serve distinct roles in the body, with educated NK cells providing immunity against MHC-deficient tumors and uneducated NK cells providing immunity against some viral infections and tumors that retain MHC expression (Orr et al, 2010; Tu et al, 2016; Zamora et al, 2017).…”
Section: Nk Cell Population Diversity As a Function Of Nature And Nurmentioning
confidence: 99%
“…This specific immune dysfunction in XLP1 patients causes the inability of NK cells to kill EBV-infected B cells (B-EBV), over-expressing their ligands (i.e., CD48 and NTB-A), with dramatic clinical consequences. Following this knowledge, we further analyzed the NK cell receptor repertoire of these patients, showing that substantial proportions of NK cells lacking any inhibitory receptor specific for self-HLA (self-NKR neg ) are present and are fully functional, indicating that inhibitory 2B4 participates to NK cell education (177). Remarkably, self-NKR neg NK cells can efficiently kill CD48 neg target cells, such as mature DC, with consequently defective antigen presentation, further exacerbating the immune defect of these patients.…”
Section: Nk Cell Education and Receptor Repertoirementioning
confidence: 99%